Outage Performances of 5G Channel Model Influenced by Barometric Pressure Effects in Yogyakarta - Solichah Larasati; Serli Ridho Yuliani; Achmad Rizal Danisya (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
Abstract — The fifth-generation cellular technology (5G) is predicted to adopt a high-frequency channel, which could lead to a new challenge, namely, wave propagation attenuation. This attenuation is affected by natural conditions, such as barometric pressure, rain rate, humidity, and vegetation density. This paper proposes a 5G channel model under the barometric pressure effect to address the issue. The channel model is obtained from series computer simulations by operating frequency of 28 GHz and real-field parameters of Yogyakarta environments. The 5G channel model frameworks consist of two steps. First, generate the instantaneous Power Delay Profile (PDP) using NYU Wireless Simulator with real-field parameters of the environment. Second, the instantaneous PDP is then used to calculate the representative PDP. PDP differs from one country to another, especially on 5G technology, because of the high-frequency band, which is sensitive to nature. To observe the barometric pressure effect, we need to generate the instantaneous PDP with minimum and maximum barometric effects. PDP value used to calculate the outage probability of channel capacity (C) is smaller than the coding rate (R), indicating a failure of detection at the receiver based on the Shannon theory. Outage probability is obtained by the cumulative distribution function of the capacity evaluated against the coding rate. Outage probability results in both scenarios can reach a point of 10-4, for coding rate ½ needs 17.649883 dB, coding rate ¾ needs 20.020953 dB, and coding rate 1 needs 22 dB. This shows that barometric does not significantly influence the performance of the 5G communication system.